Prenatal Stress and its effects of human cognition, behavior and psychopathology: A review of the literature - Ramborger, Mariano Enrique (2018)
Stress plays a fundamental role in the etiology and evolution of diseases and disorders both in the early stages of development and the adult life. Neuropsychiatric disorders such as depression, autism, ADHD and schizophrenia have a complex etiology, which is influenced by early experiences that affect the vulnerability of the individual.During early intrauterine and postnatal life, the developing organism undergoes complex physiological changes, and even small disturbances can have far-reaching consequences which can be observed even into adulthood. Currently, understanding the factors that may be affecting the organism during development is a challenge. Among the effects induced by Prenatal Stress we can mention a dysregulation of the HPA axis, an alteration of the circadian rhythm, a reduction of the hippocampal plasticity and the capacity of learning and memory among others.The effects of Prenatal Stress are widely studied in laboratory animals, but systematic research on human subjects is comparatively scarce. While studies in humans suffer from certain methodological limitations, they are currently the only way to explore some of the most complex, long-term interactions between antenatal stress and the behavioral and cognitive alterations of the offspring. This work aims to review studies about Prenatal Stress pertaining human subjects, and to explore some of the controversies arising on this field.